Analisis Implementasi Transformasi Bisnis Peternakan terhadap Kinerja PT Berdikari (PERSERO) - Anna Muslikhah Jamil; Harianto Harianto; Sahara Sahara (IPB University, 2019)
PT Berdikari (Persero) was transformed into an Animal Husbandry State Owned Company (SOE) in 2012 through the letter of State-Owned Enterprises Minister Number S-211/D1.MBU/2012 to support Government’s policies on providing animal food supply. This business transformationchanges core competencies from trading agribusiness commodities (rice, sugar, meat, platantion commodities, fertilizer, insurance, etc.) to animal husbandry. It becomes corporate transformation phase that cause financial performance anomalies. This study aims to identify the effect of business transformation towards financial performance of PT Berdikari (Persero) using statistical hypothesis testing by T-test to explore the existence of financial performance impact before and after business transformation practice. Based on State-Owned Enterprises Minister Regulation Number 1000/MBU/2012 about SOE performance assessment, there are eight indicators for assessing SOEs’ financial performance: Return on Equity (ROE), Return on Investment (ROI), Inventory Turn Over, Colection Period, Cash Ratio, Current Ratio, Total Turn Over and Capital to Total Assets Ratio. The result of hypothesis testing with 95percent degree of significance found that there are differences of ROE and Inventory Turn Over PT Berdikari (Persero) before and after transformation. Company profit was decreased and operating expenses was increased. Low level of sales revenue drives ROE, especially after business transformation. This low level of sales caused Inventory Turn Over to increased since inventories in the warehouse was cumulated.